The Emerging Roles of Pellino Family in Pattern Recognition Receptor Signaling - Zhang, E; Li, Xia (Frontiers in Immunology, 2022)
The Pellino family is a novel and well-conserved E3 ubiquitin ligase family and consists of Pellino1, Pellino2, and Pellino3. Each family member exhibits a highly conserved structure providing ubiquitin ligase activity without abrogating cell and structure-specific function. In this review, we mainly summarized the crucial roles of the Pellino family in pattern recognition receptor-related signaling pathways: IL-1R signaling, Toll-like signaling, NOD-like signaling, T-cell and B-cell signaling, and cell death-related TNFR signaling. We also summarized the current information of the Pellino family in tumorigenesis, MicroRNAs, and other phenotypes. Finally, we discussed the outstanding questions of the Pellino family in immunity.